Hubungan Karakter Anak Dan Urutan Kelahiran Dengan Perkembangan Mental Emosional Anak Prasekolah - Wahyu Eka Saputra, David; Kusbiantoro, Dadang; Harmiardillah, Sylvi (Jurnal Media Informatika, 2025)
Mental-emotional development is an important aspect of pre-school children's growth and development. This developmental process can affect their ability to interact with their social environment and face life's challenges. Many factors can influence this emotional development, two of which are the child's character and their birth order. The aim of the study was to analyse the relationship between children's character and birth order with pre-school children's mental emotional development. The research design used was correlation with a crosssectional approach. The population was 49 children and using total sampling technique. The data of this study were taken using questionnaires and observation sheets. The results showed that most children (69.4%) had a sanguinis character and almost all (85.7%) had a middle child birth order and almost all (91.8%) had normal emotional development. Based on the results of the Coeffient of Contingency test, p=0.004 and the value (c)=0.462 and the Spearman Rho test obtained the results of p=0.000 and the value of rs=0.559. This means that there is a relationship between child character and birth order with mental emotional development in preschool children. The results of this study are expected as a reference for parents in shaping the character of children who are able to interact well with others and face the challenges of life in the future and schools can use media and a fun learning system to improve children's emotional development.